A systematic review of pain outcomes reported by randomised trials of hip and knee arthroplasty. (7th June 2020) - Koyuncu, S.; Friis, C. P.; Laigaard, J.; Anhøj, J.; Mathiesen, O.; Karlsen, A. P. H.
Summary: It is difficult to pool results from randomised clinical trials that report different outcomes. We want to develop a core set of pain‐related outcomes after total hip or knee arthroplasty, the first stage of which is to systematically review published outcomes. We searched PubMed, Embase and CENTRAL for relevant trials to January 2020. We identified 165 outcomes from 565 trials with 50, 668 participants, which we categorised into six domains: pain; analgesic consumption; quality of care; adverse events; mobility; and patient‐reported outcome measures. The outcome in each domain reported by most trials was: visual analogue score for pain, 401 (71%); morphine consumption, 212 (38%); length of hospital stay, 166 (29%); nausea or vomiting, 425 (75%); range of motion, 173 (31%); and patient satisfaction score, 181 (32%). A primary outcome was reported in 281 (50%) trials: 101 (18%) trials reported consumption of rescue analgesics and 95 (17%) trials reported pain. We plan to publish a consensus on outcomes that should be reported in postoperative pain trials after hip or knee arthroplasty.